Role of the followers in the development of theories of organizational leadership - García Solarte, Mónica (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The most reviews about leadership have focused on the leader and his role in the organization. Modern research shows that the followers, as an important element of leadership, have an active role in the selection of leadership style and theory from which you evaluate a leader. From this point, the aim of this article is to identify what has been the role of followers in the development of theories of organizational leadership. In assessing the role of the follower in the development of theories of leadership, it was concluded that according to their perception, their behavior and their needs require a certain category of leader, which can be seen from each theory.